2022
DOI: 10.5045/br.2022.2022057
|View full text |Cite
|
Sign up to set email alerts
|

Association of CD40 gene polymorphisms and immune thrombocytopenic purpura in the adult Egyptian population

Abstract: Background:The pathophysiology underlying primary adult immune thrombocytopenic purpura (ITP) has not yet been identified. However, many mechanisms affect the immune system, causing defective tolerance to self-platelets and megakaryocytes. Cluster of differentiation 40 (CD40) contributes to both humoral and cell-mediated immune responses. Methods:This case-control study was conducted to detect rs4810485G>T and rs1883832C>T polymorphisms of CD40 in Egyptian patients with persistent/chronic ITP to clarify their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“… 79 Similar findings were obtained by Ellithy et al, who found that carriers of combined gene polymorphisms CD40 rs1883832 and CD40 rs4810485 have a higher risk of developing cITP. 80 …”
Section: Polymorphisms In Genes Regulating T-cell Activitymentioning
confidence: 99%
“… 79 Similar findings were obtained by Ellithy et al, who found that carriers of combined gene polymorphisms CD40 rs1883832 and CD40 rs4810485 have a higher risk of developing cITP. 80 …”
Section: Polymorphisms In Genes Regulating T-cell Activitymentioning
confidence: 99%